THE ROLE OF LOGO-FASCIAL MASSAGE IN THE CORRECTION OF SPEECH DISORDERS - Sharopova Hafiza Abdulhamitovna; Toshkuziev Ibrahim (Bright Mind Publishing, 2025)
This article examines how to form a child's speech, etiology and diagnosis of a specific speech defect, and the ways to properly perform fascial massage. The article considers the use of a modern and effective method for correcting speech disorders in children and adults, including fascial massage logs. Characterizations of fascial massage logs that distinguish them from classical logopedic massage approaches are described. A method for correcting speech disorders is described, it consists of five stages.
Keywords: Speech, logo-fascial massage, articulatory gymnastics, classical gymnastics, logo-fascial massage methods.